Highly efficient electrochemical and chemical hydrogenation of 4-nitrophenol using recyclable narrow mesoporous magnetic CoPt nanowires. Issue 40 (26th September 2016) - Serrà, Albert; Alcobé, Xavier; Sort, Jordi; Nogués, Josep; Vallés, Elisa
Abstract : Magnetically actuated CoPt nanowires show extraordinary performance for 4-nitrophenol degradation. Abstract : Toxic nitro-compounds, such as 4-nitrophenol, are one of the most common wastewater industrial pollutants. Thus, efficient ways to neutralize them are actively pursued. Here novel procedures to degrade these types of compounds based on the use of mesoporous magnetic nanowires are demonstrated. Fully-mesoporous magnetic narrow (25 nm) CoPt nanowires with an extraordinary effective area are grown using ionic liquid-in-water microemulsions in alumina templates. These mesoporous nanowires are shown to be efficient catalysts for the hydrogenation of 4-nitrophenol by electrocatalysis. Additionally, these nanowires also present exceptional conventional catalytic activity when used in conjunction with NaBH4, particularly when magnetic stirring is utilized. In fact, magnetically actuated mesoporous CoPt nanowires drastically outperform all state-of-the-art 4-nitrophenol catalysts. Additionally, given their magnetic character, these nanowires can be easily recycled and reused. Thus, the outstanding catalytic performance of mesoporous CoPt nanowires makes them excellent candidates for wastewater treatment agents.